Faithful doubt : the wisdom of uncertainty - Collins, Guy (The Lutterworth Press, 2015)
Focussing on three philosophers - Giorgio Agamben, Jacques Derrida, and Slavoj Žižek - Faithful Doubt argues that atheism can be redeeming. Far from being inhospitable to faith, doubt is increasingly necessary for theology. As well as introducing the thought of contemporary philosophers, 'Faithful Doubt' examines the significance of popular entertainment and narrative. Novels by Ursula K. Le Guin, Neal Stephenson, China Miéville, and others are read alongside 'Star Wars' and 'Battlestar Galactica'. Fiction highlights the fluid nature of the sacred and the secular. On the question of evil, 'Fai.